2018
DOI: 10.2147/ijwh.s158281
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional analysis of the endometrial cavity: how many dimensions should the ideal intrauterine device or system have?

Abstract: BackgroundThe geometrical shape of the human uterus most closely approximates that of a prolate ellipsoid. The endometrial cavity itself is more likely to also have the shape of a prolate ellipsoid especially when the extension of the cervix is omitted. Using this information and known endometrial cavity volumes and lateral and vertical dimensions, it is possible to calculate the anteroposterior (AP) dimensions and get a complete evaluation of all possible dimensions of the endometrial cavity. These are singul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Currently, research on the ECA is scarce. Goldstuck obtained the ECV using 3D US and then studied the ECA (range, 6.29 to 38.2 mm), which was derived from the ellipsoid formula (6). As stated above, the endometrial cavity does not exhibit a regular ellipsoid shape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, research on the ECA is scarce. Goldstuck obtained the ECV using 3D US and then studied the ECA (range, 6.29 to 38.2 mm), which was derived from the ellipsoid formula (6). As stated above, the endometrial cavity does not exhibit a regular ellipsoid shape.…”
Section: Resultsmentioning
confidence: 99%
“…To date, few authors have reported measurements of endometrial cavity anteroposterior diameter (ECA). Goldstuck studied the ECA, which was derived from the ellipsoid formula (6); however, the results of their study were not exact, because the shape of the uterine cavity is not an ellipse. The endometrium is central to female reproductive physiology (7).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a frame is particularly advantageous in these women. Frameless IUD, contains a very small copper, is smaller than any other IUD and better tolerated with less effect on the amount of blood loss [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Goldstruck et al [ 124 ] described high variability in size and shape of the endometrial cavity. This points out how difficult it is for an IUD to match such highly variable dimensions.…”
Section: 3d-printing Of Drug-eluting Implantsmentioning
confidence: 99%